(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
This article is an attempt to prove that the ontology, from its primary origin until the present time, is a study of Being, and it has never been in any time an existential metaphysics. We will try to prove this by an interpretive survey of the history of ontology, depending on the original texts of the philosophers themselves, starting from the Greek philosophy, passing through Medieval and Modern philosophy and ending at the Contemporary philosophy.